Enhancing Phytoextraction of HMs at Real Scale, by Combining Salicaceae Trees With Microbial Consortia - Guarino, Carmine; Paura, Bruno; Sciarrillo, Rosaria (Frontiers in Environmental Science, 2018)
We applied an integrated phytoremediation system by inoculation of rhizosphere microbes on an area of 2000 m2 that was contaminated by heavy metals. Hybrid poplar (Populus deltoids x Populus nigra) and willow (Salix purpurea subsp. lambertiana) were planted on four parcels of 500 m2. Of these, two parcels were inoculated with an autochthonous consortium specially selected and the other two were not inoculated. The analyses were carried out on plant and soil samples collected at different times: month 0 (T0), 12 (T1), 24 (T2) and 36 (Tf). Total concentrations of HMs in the roots of Populus and Salix showed significant increase in the plants with rhizosphere microflora consortium. The plants treated with the consortium have an increased enzymatic activity of antioxidants and of stress markers. All enzymes showed an important contribution in enzymatic thiol-dependent ROS scavening mechanisms, through its over-expression at time T1 and T2 and a consequent stabilization at Tf which results in adaptive mechanisms. The plant-fungi-bacterium system was a valid candidate for the implementation of phytoremediation systems in the field, since the plants showed a greater capacity for adaptation and accumulation.